If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 5x + 10 = 0 Reorder the terms: 10 + 7x + 5x = 0 Combine like terms: 7x + 5x = 12x 10 + 12x = 0 Solving 10 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 12x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 12x = 0 + -10 12x = 0 + -10 Combine like terms: 0 + -10 = -10 12x = -10 Divide each side by '12'. x = -0.8333333333 Simplifying x = -0.8333333333
| y+5=-10(X-1) | | 18x^2-47x-56=0 | | 3+(5a+5)=35 | | -1-9x=9x+19 | | 15*x^10=67 | | 7(4b-1)=-3b-2 | | 3(2m-10)=2m+10 | | 20=14m-9+3(5m) | | 17-x=3x-7 | | 8x-6=-2(6x+4)+2x | | x^5-4x^4+x^3+2=0 | | 47+3=40 | | X=45 | | y=4-xsqaured | | 16y^2+28=0 | | 10x+11y= | | x^4+5x^2+49=0 | | -(-x-5)+5(x-9)=2(x+8)-2x+5 | | 3n+2=9 | | 2x=3(1-x)-(x-1) | | 2x^3-12x^2+24x-2=0 | | 3x-(x-2)=(2x-1)(-3x+9) | | (2x-1)(-3x+9)=0 | | 2(c-2)whenc=7 | | 3x-1=4(2x-5) | | 63-4x=5x+23 | | 0.4(3k-0.6)= | | 13-9x=73-23x | | 0.05x-.6=5.3 | | 5p-6+3p=12 | | 13h+6d-9d-7h=0 | | (4x-37).12=276 |